Forest Biomass and Carbon Stock Estimation in Kumaun Himalaya using Geospatial Approach - Sharma, Richa; Chaudhry, Smita; Sharma, Neeraj Kumar (Indian Forester, 2020)
Forest types of Kumaun Himalaya were mapped using IRS-P6, AWiFS satellite data and integrated with crown cover classes to generate forest type cum crown cover map. A total of 25 categories of crown cover were obtained in 12 forest types. Sampling in different crown cover classes was carried out to measure mean stand biomass and mean crown cover in each forest type. Regression equations were developed between ground measured mean stand biomass and mean crown cover. Based on these equations mean biomass for each crown cover class was estimated. Mean biomass values were substituted for crown cover classes in forest type cum crown cover map to prepare biomass maps for the aboveground components of tree. Entire study area exhibited a total biomass of 22.18 Ã— 107 ton, of which contribution of bole, branch, twig and foliage was: 66.6%, 20.9%, 8.4% and 4.7%, respectively. The total carbon stored in the aboveground components of the tree layer existing in the study area was 11.16 Ã— 107 ton. The estimates of biomass and carbon stock are relevant in context of climate change studies and further helpful to advocate forest conservation as a carbon sink in Himalayan region.